Synthesis and antimycobacterial activity of some 2-(4-aminophenyl)-5-substituted amino-1,3,4-thiadiazole derivatives and their coupling products - KARAKUŞ, SEVGİ (MARMARA UNIV, FAC PHARMACY, 2016)
In the present study, several 2-(4-aminophenyl)-5-substituted amino-1,3,4-thiadiazoles (2a-l) and their coupling products, 2,3,4-pentanetrione-3-[4-(5-alkyl/arylamino-1,3,4-thiadiazole-2-yl)phenyl]hydrazones (3a-j) were synthesized in good yields and characterized by UV, IR, H-1-NMR, mass and elemental analysis. Antitubercular activity of the synthesized compounds was determined in vitro using the BACTEC 460 Radiometric System against Mycobacterium tuberculosis H37Rv at 6.25 mu g/mL. The antimycobacterial data of screened compounds indicated that 2-(4-aminophenyl)-5-(4-chlorophenyl)amino-1,3,4-thiadiazole 2f demonstrated the highest inhibition.
Keywords: ANTITUBERCULOSIS ACTIVITY; AGENTS; 1,3,4-THIADIAZOLE